2018
DOI: 10.1108/ijhcqa-10-2016-0153
|View full text |Cite
|
Sign up to set email alerts
|

Environmental impact reduction as a new dimension for quality measurement of healthcare services

Abstract: Purpose The purpose of this paper is to provide a detailed accounting of energy and materials consumed during magnetic resonance imaging (MRI). Design/methodology/approach The first and second stages of ISO standard (ISO 14040:2006 and ISO 14044:2006) were followed to develop life cycle inventory (LCI). The LCI data collection took the form of observations, time studies, real-time metered power consumption, review of imaging department scheduling records and review of technical manuals and literature. Find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…For example, if a patient needs CT, the environmental footprint will be 10.2–15.8 kg CO 2e per patient 39 . By contrast, the carbon footprint for MRI is 22.4 kg CO 2e per patient 40 . Finally, endoscopies are procedures with considerable environmental effects owing to waste generation, accounting for approximately 3.09 kg of waste per bed per day, which is equivalent to 3 kg CO 2e (ref.…”
Section: Health-care Carbon Footprintmentioning
confidence: 95%
“…For example, if a patient needs CT, the environmental footprint will be 10.2–15.8 kg CO 2e per patient 39 . By contrast, the carbon footprint for MRI is 22.4 kg CO 2e per patient 40 . Finally, endoscopies are procedures with considerable environmental effects owing to waste generation, accounting for approximately 3.09 kg of waste per bed per day, which is equivalent to 3 kg CO 2e (ref.…”
Section: Health-care Carbon Footprintmentioning
confidence: 95%
“…The cluster LCA is related to subthemes 'GREENHOUSE-GASES' and 'EDUCATION'. The LCA analysis has been applied in different scenarios such as healthcare [114], energy [115], agriculture [116] and manufacturing processes [117], and skills training of undergraduates about the understanding of LCA to promote SM [118].…”
Section: Thematic Network Structure Of the Cluster 'Life-cycle-assmentioning
confidence: 99%
“…Then the energy intensity was calculated. The annual energy consumption for this facility, based on the utility bills, was provided in kWh and it is equal to 1,450,692 kWh (5,222,484 MJ). The energy intensity is the total energy (in kWh or MJ) divided by the facility area (in square foot or square meter).…”
Section: Facilitymentioning
confidence: 99%
“…[3] In this research, a focus was placed on the energy consumption within aerospace manufacturing. This is an important area and while there are examples of energy intensity quantification for commercial and government sectors Bawaneh et al [4] and Esmaeili et al [5][6][7] little literature has been found on it relating to energy consumption of the entire manufacturing facility. article about the energy intensity of computer manufacturing [8], study of the impact of automation on manufacturing energy intensity [9].…”
Section: Introductionmentioning
confidence: 99%